Treatment of gastroenteritis in covid-19 children - Atif Amin, Baig; Chandrika, Murugaiah; Constance, Liew Sat Lin (2020)
SARS-CoV-2 is highly contagious and has resulted in a rapid pandemic of COVID-19 that posing a threat to public health. They are causing a severe acute respiratory syndrome and known to infect the neurological, enteric, and hepatic systems. The aim of this document is to provide recommendations for a systematic approach for the gastroenteritis treatment in COVID-19 children where most important treatment options where discussed.